Analysis of Information Technology Adoption in Polish Agriculture - Dmowski, Kamil; Bartyna, Waldemar; Stępniak, Marcin (Studia Informatica. System and information technology, 2025)
This study explores the adoption of information technology (IT) in Polish agriculture, focusing on its impact on efficiency, profitability, and farmers’ perceptions of associated costs. A survey conducted among 106 farmers from all Polish provinces assessed their use of IT tools, including farm management software and automatic machine navigation systems. The results highlight the varying degrees of IT adoption based on farm size, with larger farms demonstrating greater integration of these technologies. Farmers’ views on the cost-effectiveness of these systems were mixed, indicating room for improvement in affordability and functionality. The study underscores the potential of IT to enhance agricultural practices but notes the barriers faced by smaller farms in adopting such technologies.